2016
DOI: 10.1016/j.bbamem.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Single channel activity of OmpF-like porin from Yersinia pseudotuberculosis

Abstract: To gain a mechanistic insight in the functioning of the OmpF-like porin from Yersinia pseudotuberculosis (YOmpF), we compared the effect of pH variation on the ion channel activity of the protein in planar lipid bilayers and its binding to lipid membranes. The behavior of YOmpF channels upon acidification was similar to that previously described for Escherichia coli OmpF. In particular, a decrease in pH of the bathing solution resulted in a substantial reduction of YOmpF single channel conductance, accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Mean 5 SD (n ¼ 3). (22), and Rokitskaya et al (23) concluded that gA most likely is able to exchange between lipid bilayers, although definitive proof was lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean 5 SD (n ¼ 3). (22), and Rokitskaya et al (23) concluded that gA most likely is able to exchange between lipid bilayers, although definitive proof was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative interpretation of the results of Jones et al (12) is that the sustained channel activity was caused by direct transfer of gA from the source LUVs to the interrogated planar bilayer without vesicle fusion. Transfer of gA between lipid vesicles has been proposed previously based on comparisons of the ion release from lipid vesicles and the amount of gA/vesicle (21,22), or the reduction in gA activity after the incubation of gA-containing LUVs with an excess of gA-free vesicles (23), but see (24) for an alternative view. We therefore explored further the possibility that gA is able to undergo facile transfer from one lipid bilayer to another (whether in planar bilayers or lipid vesicles).…”
Section: Introductionmentioning
confidence: 99%
“…Pore size may vary with environmental factors, e.g., pH-sensitivity of OmpF and OmpG channels [ 44 , 45 ]. Some of the structures analyzed have been proven to be in a closed state (e.g., OmpA, OccD1 and D2).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of LPC, the OmpF-like porin of Y. pseudotubeduclosis alters its ion channel activity and the large-conductance mechanosensitive channel MscL of E. coli is trapped in the fully open state (62,63). In both cases, the mechanisms are proposed to involve intrinsic membrane curvature stress and the resulting physical distortion of the lipid bilayer induced by incorporation of the LPL.…”
Section: Function Of Lpls In the Bacterial Envelopementioning
confidence: 99%